Phosphodiesterase 9 inhibition prolongs the antiparkinsonian action of l-DOPA in parkinsonian non-human primates. (1st July 2022) - Masilamoni, Gunasingh J.; Sinon, Christopher G.; Kochoian, Brik A.; Singh, Arun; McRiner, Andrew J.; Leventhal, Liza; Papa, Stella M.
Abstract: Phosphodiesterase 9 (PDE9) degrades selectively the second messenger cGMP, which is an important molecule of dopamine signaling pathways in striatal projection neurons (SPNs). In this study, we assessed the effects of a selective PDE9 inhibitor (PDE9i) in the primate model of Parkinson's disease (PD). Six macaques with advanced parkinsonism were used in the study. PDE9i was administered as monotherapy and co-administration with l -DOPA at two predetermined doses (suboptimal and threshold s.c. doses of l -Dopa methyl ester plus benserazide) using a controlled blinded protocol to assess motor disability, l -DOPA -induced dyskinesias (LID), and other neurologic drug effects. While PDE9i was ineffective as monotherapy, 2.5 and 5 mg/kg (s.c.) of PDE9i significantly potentiated the antiparkinsonian effects of l -DOPA with a clear prolongation of the "on" state (p < 0.01) induced by either the suboptimal or threshold l -DOPA dose. Co-administration of PDE9i had no interaction with l -DOPA pharmacokinetics. PDE9i did not affect the intensity of LID. These results indicate that cGMP upregulation interacts with dopamine signaling to enhance the l -DOPA reversal of parkinsonian motor disability. Therefore, striatal PDE9 inhibition may be further explored as a strategy to improve motor responses to l -DOPA in PD. Highlights: A selective PDE9 inhibitor potentiates the antiparkinsonian effects of L-DOPA by prolonging response duration. The effect of PDE9 inhibition on motor responses of l -Dopa is not complicated by augmenting dyskinesias. Effects of PDE9 inhibition that lead to increased levels of cGMP suggest a distinct cGMP interaction with dopamine signaling. In addition to therapeutic implications, these data challenge our understanding of cGMP-mediated dopamine signaling.